2018
DOI: 10.3389/fpsyg.2018.00443
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in Chronotype and Preferred Time for Sex and Its Role in Relationship Quality and Sexual Satisfaction

Abstract: Recently, the issue of diurnal preferences has been increasingly studied within the context of romantic relationships and sexual functioning. In the present paper we apply a dyadic design to investigate the role of romantic partners' diurnal preferences in determining a variety of relationship outcomes. A sample of 91 heterosexual couples completed a set of questionnaires measuring relationship satisfaction, sexual satisfaction, and morningness-eveningness, and answered questions regarding their actual and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 64 publications
1
16
0
1
Order By: Relevance
“…Moreover, we also observed that sleeping features are highly correlated within a couple. This correlation is stronger during when the couple’s child is younger but dilutes at 6 years of age postpartum in our data, confirming that couples tend to have similar chronotype and sleeping habits in the earliest phases of their relationship, as already observed by other studies [ 3 ]. On one hand, within couple correlations of midpoint of sleep, time of getting out of bed and sleep onset are positive and particularly strong, especially during free days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, we also observed that sleeping features are highly correlated within a couple. This correlation is stronger during when the couple’s child is younger but dilutes at 6 years of age postpartum in our data, confirming that couples tend to have similar chronotype and sleeping habits in the earliest phases of their relationship, as already observed by other studies [ 3 ]. On one hand, within couple correlations of midpoint of sleep, time of getting out of bed and sleep onset are positive and particularly strong, especially during free days.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, couples tend to have similar chronotype and sleeping habits [ 2 ]. Secondly, the chronotype similarity positively affects the partnership relationship between the two people in the couple [ 3 ]. Furthermore, the association between chronotype similarity and relationship satisfaction operates as a function of the relationship stage.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect to consider is sexual opinion. Attitudes towards sexuality are related to morning or evening preferences [ 17 , 18 ]. The erotophobia–erotophilia dimension, both of which are a learned disposition to respond to sexual stimuli, is used to measure sexual opinion.…”
Section: Introductionmentioning
confidence: 99%
“…The erotophobia–erotophilia dimension, both of which are a learned disposition to respond to sexual stimuli, is used to measure sexual opinion. Erotophobia entails the response with more negative attitudes towards the sexual stimulus and feelings of avoidance, and erotophilia is an opinion contrary to erotophobia, a positive attitude towards the sexual stimulus, with more favourable emotions and evaluations leading to a greater search for sexual stimuli [ 17 , 18 , 19 ]. There seems to be a higher evening peak of sexual activity and desire [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…During night-time, after the working hours, individuals are at their peak tiredness. This disrupts self-regulation and predisposes to impulsive behaviors, succumbing to immediate pleasures, such as cravings for food ( Sevincer et al, 2016 ), alcohol and club/party drug use ( Millar et al, 2019 ), and sexual intercourse ( Refinetti, 2005 ; Jocz et al, 2018 ). Indeed, evening-oriented individuals have lower self-control ( Digdon and Howell, 2008 ), which mediates their higher present orientation and instant gratification ( Milfont and Schwarzenthal, 2014 ), are more impulsive ( Cross, 2010 ), are more hedonistically present-oriented ( Nowack and Van Der Meer, 2013 ; Stolarski et al, 2013 ; Borisenkov et al, 2019 ), use more alcohol and club/party drugs ( Millar et al, 2019 ), and tend to smoke more ( Randler, 2008 ; Wittmann et al, 2010 ; Patterson et al, 2016 ) than other chronotypes.…”
Section: Night-time Adaptive Challengesmentioning
confidence: 99%